art.pics Database: An Open Access Database for Art Stimuli for Experimental Research - Thieleking, Ronja; Medawar, Evelyn; Disch, Leonie; Witte, A. Veronica (Frontiers in Psychology, 2020)
While art is omnipresent in human history, the neural mechanisms of how we perceive, value and differentiate art has only begun to be explored. Functional magnetic resonance imaging (fMRI) studies suggested that art acts as secondary reward, involving brain activity in the ventral striatum and prefrontal cortices similar to primary rewards such as food. However, potential similarities or unique characteristics of art-related neuroscience (or neuroaesthetics) remain elusive, also because of a lack of adequate experimental tools: the few available collections of art stimuli often lack standard image definitions and normative ratings. Therefore, we here provide a large set of well-characterised, novel art images for use as visual stimuli in psychological and neuroimaging research. The stimuli were created using a deep learning algorithm that applied different styles of popular paintings (based on artists such as Klimt or Hundertwasser) on ordinary animal, plant and object images which were drawn from established visual stimuli databases. The novel stimuli represent mundane items with artistic properties with proposed reduced dimensionality and complexity compared to paintings. In total, 2332 novel stimuli are available open access as “art.pics" database at https://osf.io/BTWNQ/ with standard image characteristics that are comparable to other common visual stimuli material in terms of size, variable colour distribution, complexity, intensity and valence, measured by image software analysis and by ratings derived from a human experimental validation study (n = 1296 (684f), age 30.2 ± 8.8 y.o.). The experimental validation study further showed that the art.pics’ images elicit a broad and significantly different variation in subjective value ratings (i.e., liking, wanting) as well as in recognisability and arousal across different art styles and categories. Researchers are encouraged to study the perception, processing and valuation of art images based on the art.pics database which also enables real reward remuneration of the rated stimuli (as art prints) and a direct comparison to other rewards from e.g. food or money.